Incidencia de la red inalámbrica de radio Latacunga - Sánchez Lema, Kléber Hernán (2010)
This research was made in order to permits, people know about its importance benefits, with wireless net supported by Latacunga Radio Station in Cotopaxi province to get benefits with rural areas from Pastocalle, Mulalillo and Sigchos. Also it permits to know about the social context, the management of technical elements that conform and the benefits that gives to the society and community in communication & development.